Pencitraan â€œAman dan Damaiâ€ pada Aksi Reuni 212 - Achfandhy, Mochammad Irfan (LENTERA, 2020)
The mass demonstration of Aksi Reuni 212 attracted large amount of controversy among Indonesian people due news framing of media which signify some aspects and suppress other aspects of the event thus effectively making the coverage subjective. This article aims at understanding the construction of news framing on the subject of Aksi Reuni 212, especially regarding the process of securing permission to perform the mass demonstration, by online news portals Detik.com and Liputan6.com. It also aims at revealing the differences between the two news portals regarding their news framing construction. Model of framing analysis by William A. Gamson and Andre Modigliani is applied to analyze data in interpretative and qualitative manner. Findings reveal that news coverages from Detik.com were more inclined to the preparedness of the government to deal with risks pertaining to national security posed by the event. Liputan6.com, on the other hands, framed the event of Aksi Reuni 212 as a regular, instead of extraordinary, demonstration event that does not need special attention regarding security threats it might brought. Despite differences in terms of how they framed the event, both news portals framed the event positively.Keywords: Aksi Reuni 212, image, and online media.